2017
DOI: 10.1123/ijspp.2016-0334
|View full text |Cite
|
Sign up to set email alerts
|

Managing the Training Load in Adolescent Athletes

Abstract: While historically adolescents were removed from their parents to prepare to become warriors, this process repeats itself in modern times but with the outcome being athletic performance. This review considers the process of developing athletes and managing load against the backdrop of differing approaches of conserving and maximizing the talent available. It acknowledges the typical training "dose" that adolescent athletes receive across a number of sports and the typical "response" when it is excessive or not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
43
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(49 citation statements)
references
References 49 publications
(62 reference statements)
1
43
0
Order By: Relevance
“…It facilitates monitoring of training [22] and recovering loads in athletes [23], the assessment of sleep quality [24] and the impacts of physical activity on health indicators in diverse groups of people [25,26]. There is also an important contribution to maintaining young athletes engaged in physical activities, thus guaranteeing longevity to their careers [27]. In addition, the online feedback and constant rewards and encouragement provided by wearable technology helps on the identification of progress and health status.…”
Section: Introductionmentioning
confidence: 99%
“…It facilitates monitoring of training [22] and recovering loads in athletes [23], the assessment of sleep quality [24] and the impacts of physical activity on health indicators in diverse groups of people [25,26]. There is also an important contribution to maintaining young athletes engaged in physical activities, thus guaranteeing longevity to their careers [27]. In addition, the online feedback and constant rewards and encouragement provided by wearable technology helps on the identification of progress and health status.…”
Section: Introductionmentioning
confidence: 99%
“…On average, the athletes had been playing beach volleyball for M = 3.7 years ( SD = 1.80, Min = 1, Max = 8). They reported to practice M = 11.7 hours per week ( SD = 5.5, Min = 5, Max = 40), a reasonable amount of training for adolescent athletes [30]. Thirty-six players (58.1%) stated that they normally used the jump float serve, the others reported to use the float serve.…”
Section: Methodsmentioning
confidence: 99%
“…28 In adolescent Australian Rules football, Henderson et al 29 concluded that appropriate training load management was necessary in order to develop appropriate return to play programmes following injury and that the management of training load in adolescent athletes was necessary to ensure a longer-term participation in sport. 30…”
Section: Subsequent and Recurrent Injurymentioning
confidence: 99%